A look into preservice teachers' responses to students' misbehavior: What roles do students' gender and socioeconomic status play?. (December 2022) - Glock, Sabine; Kleen, Hannah
Abstract: Teachers' perceptions of and intervention strategies for dealing with students' misbehavior differ depending on various student characteristics such as gender. In Study 1, we investigated whether preservice teachers intervene differently when students' were talking out of turn, depending on students' socioeconomic status (SES) and gender. Results showed that the participants were more likely to intervene when the student had low SES. In Study 2, the student misbehavior was that students repeatedly forgot their homework. Study 2 showed that preservice teachers were more likely to use a talk as the intervention strategy for students with high SES and were more likely to ask for help for students with low SES. Preservice teachers indicated the student's parents as the main causes of student's misbehavior independent of the student's SES. The results are discussed with regard to social disparities in the educational system. Highlights: Preservice teachers intervened more likely in low SES students' misbehavior. Intervention strategies differed depending on students' SES. Preservice teachers preferred to talk to high SES students. Preservice teachers sought for help when dealing with low SES students. Independent of SES, parents are perceived as main cause for students' misbehavior.